Democratic Republic of the Congo : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper describes the three phases of IMF engagement in the Democratic Republic of Congo (DRC) with a view to drawing lessons that could prove useful in identifying objectives and policies for a medium-term program that could be supported through a successor Poverty Reduction and Growth Facility arrangement. The paper describes recent developments in the financial sector of the DRC and offers suggestions for fostering financial deepening. It addresses the agenda for structural fiscal reforms over the next five years. It also presents an overview of structural fiscal issues.